Geosynthetics in Civil and Environmental Engineering Geosynthetics Asia 2008 Proceedings of the 4th Asian Regional Conference on Geosynthetics in Shanghai, China - Li, Guang-xin; Chen, Yunmin; Tang, Xiaowu (Springer Berlin Heidelberg : Imprint: Springer, 2009)
Geosynthetics in Civil and Environmental Engineering presents contributions from the 4th Asian Regional Conference on Geosynthetics held in Shanghai, China. The book covers a broad range of topics, such as: fundamental principles and properties of geosynthetics, testing and standards, reinforcement, soil improvement and ground improvement, filter and drainage, landfill engineering, geosystem, transport, geosynthetics-pile support system and geocell, hydraulic application, and ecological techniques. Special case studies as well as selected government-sponsored projects such as the Three Gorges Dam, Qinghai-Tibet Railway, and Changi Land reclamation project are also discussed. The book will be an invaluable reference in this field.